The worker owner: identity and collective action in the metal mechanical sector - Pineda Duque, Javier Armando (Sociedad y Economía, 2011)
This article argues that the creation of a micro business association of male owners in the metal mechanical sector in Bogota constituted a specific process of creation of a masculine identity that shaped its collective action. This new identity emerges from their diverse subjective and material conditions as workers as well as owners. Using insights from a poststructuralist theoretical legacy and pro-feminists studies on masculinities, the article uses interview data with owners to analyze the relations that gave rise to the collective identity of this group of men, and discusses its relevance to development processes.